Analysis of general characteristics of transmission error in helical gears and its effects on gear noise and vibration / Edzrol Niza Mohamad - Edzrol Niza , Mohamad (2013)
In this thesis, a general model for the tooth meshing of gears is proposed; in which a quasi-infinite elastic model composed of springs with stiffness peculiar to the gear is incorporated. Also, the concept of potential gear noise, which is a noise to express directly the effect of tooth flank form of gear on the gear noise, is proposed and a sensory evaluation method is also proposed to evaluate sound level, noise quality and noise. The influence of tooth flank form deviation on transmission error is further investigated by using this model. The qualitative characteristic of the transmission error of gears with convex tooth flank form deviation is determined by the actual contact ratio and qualitative elements of gears; i.e. tooth flank form deviation and the distribution of stiffness. It can be concluded that the proposed sensory evaluation method of potential gear noise could enable gear designers to experience directly the effect of tooth flank form on the noise quality